Znam was wszystkich - Ambroziewicz, Jerzy (Warszawa : "BGW", 1993)
An autobiography of a well-known Polish journalist.
Includes index.
Keywords: Ambroziewicz, Jerzy; Journalists -- Poland -- Biography; Poland -- Politics and government -- 1945-